Employee e-Recruitment using the Simple Additive Weighting (SAW) Algorithm at PT Krakatau IT - Megayanti, Anita; Ritonga, Roy Amrullah; Rizqi, Via Fajriyatin (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
Recruitment aims to get the right people according to criteria that suit the company's conditions and needs. Currently in Krakatau IT the recruitment system is implemented manually using the stages of receiving files in hardcopy or still using company email, carrying out written tests directly in paper form. This requires a long time in the process of file selection and assessment of test results. To overcome this problem, an online recruitment system is needed, starting from publishing job requirements/vacancies, selection stages and online assessments. This e-recruitment can make decision making easier, from identifying problems to selecting the right data. The decision-making methodology in designing e-recruitment uses the simple additive weighting (SAW) method can help improve the fit between employees and their roles, which can contribute to better performance so that employee selection is based on criteria that match job requirements.